Modifying landing mat material properties may decrease peak contact forces but increase forefoot forces in gymnastics landings - Mills, C.; Yeadon, M. R.; Pain, M. T. G. (Sports Biomechanics, 2010)
This study investigated how changes in the material properties of a landing mat could minimise ground reaction forces (GRF) and internal loading on a gymnast during landing. A multi-layer model of a gymnastics competition landing mat and a subject-specific seven-link wobbling mass model of a gymnast were developed to address this aim. Landing mat properties (stiffness and damping) were optimised using a Simplex algorithm to minimise GRF and internal loading. The optimisation of the landing mat parameters was characterised by minimal changes to the mat's stiffness ( < 0.5%) but increased damping (272%) compared to the competition landing mat. Changes to the landing mat resulted in reduced peak vertical and horizontal GRF and reduced bone bending moments in the shank and thigh compared to a matching simulation. Peak bone bending moments within the thigh and shank were reduced by 6% from 321.5 Nm to 302.5 Nm and GRF by 12% from 8626 N to 7552 N when compared to a matching simulation. The reduction in these forces may help to reduce the risk of bone fracture injury associated with a single landing and reduce the risk of a chronic injury such as a stress fracture.